Marginal cost of carbon sequestration through forest afforestation of agricultural land in the southeastern United States. (15th June 2022) - Obembe, Oladipo S.; Hendricks, Nathan P.
Abstract: One tool to mitigate climate change is to sequester carbon through changes in land use. The purpose of this study is to analyze the cost‐effectiveness of carbon sequestration through afforestation of cropland via the Conservation Reserve Program (CRP) in the United States. We use the correlated random effects (CRE) probit model to estimate the impact of an increase in the CRP rental payments on land use transitions between cropland and forest. Our estimates are used to simulate land use change and carbon sequestration supply curves over different time horizons. Increasing the CRP rent to reflect the social cost of carbon of 154/tonne of carbon increases annual carbon sequestered by 7.42 million tonnes, 23.58 million tonnes, and 34.96 million tonnes over 1, 5, and 10‐year horizons.